Carbapenemase producing Enterobacteriaceae in intensive care units in Ecuador: Results from a multicenter study - Carmen Soria-Segarra; Claudia Soria-Segarra; Angel Catagua-González; José Gutiérrez-Fernández (Journal of Infection and Public Health, 2020)
Introduction: Carbapenemase-producing Enterobacteriaceae (CPE) are of global concern due to the growing number of patients who acquire them and their association with high mortality rates. Although there are some reports of endemicity in developing countries, little is known about this microorganism, and Ecuador is not an exception. Subsequently, our objective was to clinically and molecularly characterize carbapenemase producing-Enterobacteriaceae in intensive care units (ICUs) in Guayaquil, Ecuador. Methods: To determine CPE colonization, we obtained perineal and inguinal swabs from patients admitted to seven intensive-care adult units in Guayaquil-Ecuador between February and April 2016. The Centers for Disease Control and Prevention (CDC) laboratory protocol and chromogenic agar were used to process the cultures. Polymerase chain reaction was used to confirm carbapenemase production. Genotypic analysis was performed by Multilocus Sequence Typing (MLST) and pulsed-field electrophoresis (PFEG). Demographic and clinical data were obtained from the electronic charts and patient’s relatives. Results: Six hundred seventy-seven patients were included in the study, of whom 255 were colonized/infected by CPE. The CPE prevalence was 37.67%. Previous use of antimicrobials, use of invasive procedures and being burned at admission were associated with CPE. The most frequent infection was found after a surgical procedure. Klebsiella pneumoniae (n = 249) was the predominant microorganism harbouring blaKPC, followed by Enterobactercloacae (n = 8), Klebsiella aerogenes (n = 4), Escherichia coli (n = 4) and Klebsiella oxytoca (n = 1). NDM was present in Proteus mirabilis. The strains were distributed in 19 sequence types (ST), and 10 were not reported previously in Ecuador. ST 258 was the sequence type isolated most frequently. Conclusion: This study shows a high prevalence of CPE in ICUs, particularly K. pneumoniae blaKPC ST 258. The identification of KPC alleles may help to understand the routes of dissemination and control spread within ICUs in Guayaquil, Ecuador. Keywords: Carbapenemase, Intensive care units, Prevalence